STRUKTUR MODAL DAN KINERJA KEUANGAN BANK DI INDONESIA - Afik Maulana, Alfian; Anita Sari, Dian (Publika Citra Media, 2024)
This research aims to investigate how the capital structure of banks in Indonesia is related to the level of profitability, taking into account company size and the overall impact of the Covid-19 pandemic and whether the increase in capital (debt) provided by the Indonesian government affects bank profitability, providing new results. . considering the increased credit risks resulting from the pandemic. This study fulfills the research objectives by building a broad framework regarding the influence of liquidity, capital adequacy, credit risk, tax protection and ownership structure on bank financial performance. This research uses regression todetermine the effect of leverage, company size and the Covid-19 pandemic on banking profitability. Data for 38 public banks taken from the Bloomberg Terminal in 2014-2021. The research results show that leverage has a positive effect on banking profitability, while company size has a negative effect on leverage and profitability. High debt levels pressure management to meet shareholders' required returns. Large banks prefer risk-free government bonds rather than providing loans to creditors, especially when economic conditions are uncertain. The Covid-19 pandemic has no effect on banking profitability